2006
DOI: 10.1128/iai.74.4.2366-2372.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Responses to Migrating Brugia pahangi Third-Stage Larvae

Abstract: Despite being central to parasite establishment and subsequent host pathological and immunologic responses, host-parasite interactions during early third-stage filarial larva (L3) migration are poorly understood. These studies aimed to define early tissue migration of Brugia pahangi L3 in the gerbil (Meriones unguiculatus) and measure host cellular responses during this period. Gerbils were intradermally inoculated in the hind limb with 100 B. pahangi L3, and necropsies were performed at various times. At 3 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…LC typically produce cytokines when activated. That the L3 failed to induce cytokine secretion (except IL-6) finds support in previous studies of B. malayi infection in jirds, where a transient neutrophil infiltrate was found surrounding the L3 in the dermis, a process that was preceded by increases in IL-6 and TNF-␣ mRNAs (21). IL-10 is another cytokine thought to be involved in suppression of the immune response to filarial parasites (22); however, whether IL-10 is produced in the skin following filarial infection is still being defined.…”
Section: Discussionsupporting
confidence: 71%
“…LC typically produce cytokines when activated. That the L3 failed to induce cytokine secretion (except IL-6) finds support in previous studies of B. malayi infection in jirds, where a transient neutrophil infiltrate was found surrounding the L3 in the dermis, a process that was preceded by increases in IL-6 and TNF-␣ mRNAs (21). IL-10 is another cytokine thought to be involved in suppression of the immune response to filarial parasites (22); however, whether IL-10 is produced in the skin following filarial infection is still being defined.…”
Section: Discussionsupporting
confidence: 71%
“…Earlier studies by Ah and his coworkers (1973) demonstrated that vector derived Brugia pahangi L3 are capable of extensive rapid migration through a variety of tissue types. In order to quantitatively study this early migration, an in vivo intradermal inoculation model has been established using B. pahangi infections in gerbils (Chirgwin et al, 2006; Porthouse et al, 2006). In this model, L3s are required to move through the connective tissues of the skin prior to establishment in the lymphatics mimicking the natural early L3 migration pattern more closely than infections induced by either subcutaneous and intraperitoneal (IP) inoculations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the only fully permissive rodent host of Brugia species, the Mongolian jird, demonstrated that L3 rapidly migrated from the site of injection in the hind limb to the lymphatic system, with the majority of developing adults establishing in the lymphatics of the spermatic cord [27,28]. In the present study, we observed sections through filarial worms in the local lymphatic vessels of the infected limb at the latest time point examined (21 days p.i.)…”
Section: Discussionmentioning
confidence: 54%